Crash Simulation of Lower Limb with Motorcycle Basket - How, C. K.; Harwant Singh,; Megat Ahmad, Megat Mohamad Hamdan; Radin Sohadi, Radin Umar; Salem Hamouda, Abdel Magid (2001)
Lower limb injuries are the main cause of temporary and permanent disability among motorcyclist in Malaysia. They cause non-fatal but serious injuries requiring hospitalization. Detailed studies on factors influencing lower limb injuries are justified in an attempt to reduce the occurrence of these injuries. This study present a computer simulation of the crash behavior of the basket of a small-engined motorcycle with the lower limb using finite element (FE) methods. The result suggests that the extensive deformation of the motorcycle basket may reduce the risk of injury to the lower limb. The behavior of the basket during collision is analogous to the crimple zone of automobiles.